The Influence of Personality Traits on School Bullying: A Moderated Mediation Model - Zhang, Yun; Li, Zuoshan; Tan, Yalan; Zhang, Xi; Zhao, Qingyu; Chen, Xin (Frontiers in Psychology, 2021)
We recruited 1631 middle and high school students to explore the relationship of personality traits and school bullying and the moderated and mediating role of self-concept and loneliness between personality traits and school bullying. Results showed that (1) neuroticism had a significant positive predictive effect on being bullied, extroversion had a significant negative predictive effect on being bullied, and agreeableness had a significant negative predictive effect on bullying/being bullied; (2) loneliness played a mediating role between neuroticism and bullied behaviors, extroversion and bullying behaviors, and agreeableness and bullying/bullied behaviors; (3) self-concept played a moderated role in the mediation pathway of loneliness in neuroticism, extraversion, agreeableness and bullying behaviors. Therefore, to reduce the frequency of school bullying among adolescents, we should not only reduce their level of loneliness but also improve their level of self-concept.